DETERMINATION OF OVULATION TIME IN GAYO MARES BASED ON IMAGE OF PREOVULATORY FOLLICLE GROWTH - Juli Melia; A Amrozi; Iman Supriatna; Muhammad Agil (Universitas Syiah Kuala, 2023)
This study aimed to obtain the ultrasound image of preovulatory follicle growth in gayo mares to predict the ovulation time. This study used three Gayo mares and one gayo stallion for teaser aged 5-10 years and weighed 200-250 kg. Preovulatory follicle growth was observed using transrectal ultrasonography which was performed when the dominant follicle size was ≥ 3.5 cm. Observations were made for 3 consecutive estrous periods on gayo mares at relatively the same time. The absence of previous follicular appearance and the presence of hypoechoic area in the same ovary indicate that ovulation has occurred. The result revealed that the diameter of preovulatory follicle of gayo mares was 4.02±0.32 to 5.05±0.04 cm. There was no significant follicle growth in the last 48 hours before ovulation and the preovulatory follicle shape altered from spherical to pearshape. Many small follicles (2 cm in diameter) were observed in peripheral area of the ovary indicated the recruitment of follicles which form the first follicular wave. To conclude, the alteration in the size and pearshape of preovulatory follicle and the recruitment of small follicles can be used as a marker to determine the time of ovulation on gayo mares.